2004
DOI: 10.1210/jc.2004-0643
|View full text |Cite
|
Sign up to set email alerts
|

Stockpiling of Transitional and Classic Primary Follicles in Ovaries of Women with Polycystic Ovary Syndrome

Abstract: Recently, we proposed an oocyte-growth differentiation factor-9 hypothesis that predicts alterations in the initial stages of folliculogenesis in polycystic ovary syndrome (PCOS) ovaries. Here, we test this hypothesis by scoring the composition of follicles in normal and PCOS ovaries. Follicles were classified as primordial, transitional primary, classic primary, secondary, and Graafian. A total of 2274 follicles were scored. The total number of growing follicles was significantly greater in PCOS ovaries than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
0
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(127 citation statements)
references
References 60 publications
8
102
0
17
Order By: Relevance
“…It is not too difficult to identify biochemical pathways that may be disrupted in PCOS. There is evidence for an intrinsic disorder of ovarian folliculogenesis, [45][46][47] constitutive hypersecretion of androgens by theca cells 48,49 and disordered secretion and action of insulin 50 (Figure 1). There are, however, obvious problems in searching for candidate genes in PCOS: the heterogeneous nature of the syndrome has given rise disagreement about definition and diagnostic criteria; in addition expression of features of PCOS occurs predominantly in women of reproductive age and there is no clear male phenotypeFboth of which make family-based studies difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It is not too difficult to identify biochemical pathways that may be disrupted in PCOS. There is evidence for an intrinsic disorder of ovarian folliculogenesis, [45][46][47] constitutive hypersecretion of androgens by theca cells 48,49 and disordered secretion and action of insulin 50 (Figure 1). There are, however, obvious problems in searching for candidate genes in PCOS: the heterogeneous nature of the syndrome has given rise disagreement about definition and diagnostic criteria; in addition expression of features of PCOS occurs predominantly in women of reproductive age and there is no clear male phenotypeFboth of which make family-based studies difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Anovulation reflects the arrest of follicle development in the late antral stages but recent work from our group (Webber et al 2003), and that of Erickson and colleagues (Maciel et al 2004), has highlighted a disorder of early, preantral follicle development. The mechanism of disordered early folliculogenesis in polycystic ovaries remains uncertain but exposure to excess androgen must be considered as a possible aetiological factor.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenotype was also observed in sheep with homozygous mutations in GDF9 [18][19][20]. GDF9 might also play a role at the primary stage in human folliculogenesis, as follicles of women with PCOS have decreased GDF9 expression and demonstrate a slowing of the primary to secondary follicle transition [21][22][23]. Studies to define GDF9 effects on follicle growth in culture have shown mixed results.…”
Section: Introductionmentioning
confidence: 53%
“…Sustained growth of early follicles-specifically, late primary and early secondary follicles-to the antral stage has been achieved in vitro with organ culture [24,[43][44][45] or coculture of isolated follicles with ovarian stromal cells [46][47][48][49], mouse embryonic fibroblasts [50], multiple other follicles [25], or supplemented media [51]. Together, these findings suggest that follicle growth at the primary and early secondary stages is enhanced by, and perhaps dependent upon, factors from the surrounding ovarian environment in addition to the critical role played by the oocyte-derived factor GDF9 [6,7,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%